Economic evaluation and health care. What does it mean? - Robinson, R (1993)
Ever since the concept of value for money in health care was introduced into the NHS, economic terms and jargon have become part of our everyday lives--but do we understand what the different types of economic evaluation all mean, particularly those that sound similar to the uninitiated? This article introduces readers to the purpose of economic evaluation, and briefly explains the differences between cost-minimisation analysis (used when the outcomes of the procedures being compared are the same); cost-effectiveness analysis (used when the outcomes may vary, but can be expressed in common natural units, such as mm Hg for treatments of hypertension); cost-utility analysis (used when outcomes do vary--for example, quality of life scales); and cost-benefit analysis (used when a monetary value is being placed on services received). Further articles will deal with each one in more detail.